REGULATION OF PULMONARY OXYGEN EXCHANGE USING THERAPEUTIC PHYSICAL EDUCATION - Yakubova Guyokhan; Khaydaraliyev Khurshid; Alijonova Mahliyokhan (Journals Park Publishing, 2023)
The higher the maximum oxygen demand of an athlete, the greater the chance to catch a high speed in the distance, and the higher the sports result. For example, In men who do not play sports, the maximum oxygen requirement is 3-3.5l-min. In highly qualified long-distance athletes, this indicator is 5-6l-min.
Keywords: Pulmonary oxygen exchange, physiological capacity, physiological capacity , maximal capacity, submaximal capacity, high capacity, moderate capacity, physiological responses, physical load, cyclic exercise, lactate or phosphogenic, glycolytic, aerobic or oxygen.